Basidiomycete DyPs: Genomic diversity, structural–functional aspects, reaction mechanism and environmental significance - Linde, Dolores; Ruiz-Dueñas, Francisco J.; Fernández-Fueyo, Elena; Guallar, Victor; Hammel, Kenneth E.; Pogni, Rebecca; Martínez, Angel T. (Archives of biochemistry and biophysics, 2015)
[Display omitted] •Dye-decolorizing peroxidase (DyP) genes were mined from basidiomycete genomes.•Structural–functional studies show a conserved tryptophan involved in catalysis.•Marginal activity after tryptophan substitution suggests additional oxidation sites.•DyP one-electron oxidation likely suffices for substituted anthraquinone cleavage.•DyPs have only marginal activity on nonphenolic lignin model dimers. The first enzyme with dye-decolorizing peroxidase (DyP) activity was described in 1999 from an arthroconidial culture of the fungus Bjerkandera adusta. However, the first DyP sequence had been deposited three years before, as a peroxidase gene from a culture of an unidentified fungus of the family Polyporaceae (probably Irpex lacteus). Since the first description, fewer than ten basidiomycete DyPs have been purified and characterized, but a large number of sequences are available from genomes. DyPs share a general fold and heme location with chlorite dismutases and other DyP-type related proteins (such as Escherichia coli EfeB), forming the CDE superfamily. Taking into account the lack of an evolutionary relationship with the catalase–peroxidase superfamily, the observed heme pocket similarities must be considered as a convergent type of evolution to provide similar reactivity to the enzyme cofactor. Studies on the Auricularia auricula-judae DyP showed that high-turnover oxidation of anthraquinone type and other DyP substrates occurs via long-range electron transfer from an exposed tryptophan (Trp377, conserved in most basidiomycete DyPs), whose catalytic radical was identified in the H2O2-activated enzyme. The existence of accessory oxidation sites in DyP is suggested by the residual activity observed after site-directed mutagenesis of the above tryptophan. DyP degradation of substituted anthraquinone dyes (such as Reactive Blue 5) most probably proceeds via typical one-electron peroxidase oxidations and product breakdown without a DyP-catalyzed hydrolase reaction. Although various DyPs are able to break down phenolic lignin model dimers, and basidiomycete DyPs also present marginal activity on nonphenolic dimers, a significant contribution to lignin degradation is unlikely because of the low activity on high redox-potential substrates.